2018
DOI: 10.3390/ijerph15030416
|View full text |Cite
|
Sign up to set email alerts
|

Biotoxicity of TiO2 Nanoparticles on Raphidocelis subcapitata Microalgae Exemplified by Membrane Deformation

Abstract: TiO2 nanoparticles (NPs), which are mainly used in consumer products (mostly cosmetics), have been found to cause ecotoxic effects in the aquatic environment. The green algae Raphidocelis subcapitata, as a representative of primary producers of the freshwater ecosystem, has been frequently used to study the effects of metal oxide NPs. An ecotoxicity study was conducted herein to investigate the effects of TiO2 NPs on survival and membrane deformation of algal cells. Five different concentrations of nano-TiO2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…Othman et al [ 53 ] showed an enhanced stability of NPs with higher zeta potential magnitude. Ozkaleli and Erdem [ 26 ] reported a moderate stability of TiO 2 NPs in a very soft synthetic surface water samples with an ionic strength of 0.5 mM. In our results, a moderate stability was also achieved in algae+TiO 2 NP solutions.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Othman et al [ 53 ] showed an enhanced stability of NPs with higher zeta potential magnitude. Ozkaleli and Erdem [ 26 ] reported a moderate stability of TiO 2 NPs in a very soft synthetic surface water samples with an ionic strength of 0.5 mM. In our results, a moderate stability was also achieved in algae+TiO 2 NP solutions.…”
Section: Resultssupporting
confidence: 76%
“…TiO 2 has an activation wavelength between 376 and 413 nm in the UV range of the electromagnetic spectrum [ 12 , 13 , 14 , 15 ]. Studies have shown the effects of UV radiation [ 16 , 17 , 18 , 19 ], solar simulated light [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and natural sunlight [ 27 , 28 ] with TiO 2 NP on aquatic organisms in terms of mortality, reduced growth, and DNA deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NPs can also accumulate in the cell membrane and lead to cell wall depression, which causes changes in cell membrane permeability, until cell apoptosis occurs [20]. Nanoparticles have been found to increase lipid peroxidation in cell membranes, resulting in membrane structure deformation [55]. In the cytotoxicity study of TiO 2 NPs toward Scenedesmus obliquus, plasmolysis and dentate cell membrane were observed.…”
Section: Effect Of Nps On the Cell Membranementioning
confidence: 99%
“…Diverse photocatalytic nanomaterials such as TiO2, AgNps, ZnO, CuO, CeO have been investigated using different species of algae [31,179,185,186,187,188,189,190].…”
Section: Algaementioning
confidence: 99%